THE IMPLEMENTATION OF QUALITY MANAGEMENT IN IMPROVING EDUCATORS' COMPETENCE AT MADRASAH TSANAWIYAH ALWASHLIYAH GADING IN TANJUNGBALAI - Taufik Azhar Manurung (UIN Sumatera Utara Medan, 2022)
This study aims to analyze the implementation of quality management to improve teacher competence at MTs Alwashliyah Gading in Tanjungbalai City. This research was conducted using a descriptive qualitative research method with a naturalistic qualitative approach. The findings indicate that the planning implemented at MTs Alwashliyah Gading in Tanjungbalai is based on the needs that must be met in anticipating the shortcomings of each teacher personnel, such as competencies that need to be improved, and also maintaining quality to optimize the quality of education services. Efforts made by madrasas and leaders in improving the competence of teachers/educators include enforcing discipline against teachers, holding meetings and discussions on an ongoing basis, providing supportive enthusiasm in improving the competence of teachers, and providing rewards for teachers who excel as well as giving punishment for undisciplined teachers. The quality management process to improve teacher competence at MTs Alwashliyah Gading in Tanjungbalai is going well, in teacher discipline the rules have been made by the leadership in such a way and make continuous improvements, and teachers also comply with these rules.